Challenges of Distance Teaching Implementation in Developing Content: Reports from A Senior High School Teacher - Wendi Kusriandi; Januarius Mujiyanto; Dwi Rukmini; Sri i Wuli Fitriat (Universitas Negeri Semarang, 2022)
Apart from having a long teaching experience, implementing distance teaching is a challenge. Four stages should be developed in developing content: a constructivist approach, a reflective approach, independent learning, and experiential learning. The purpose of this study is to report how teachers develop content in the implementation of distance learning. This research is a qualitative descriptive study. The participant of this study is one of the senior English teachers at one of the favorite high schools in Kuningan district, West Java. The results of this study are 50/60% of students still have difficulty using some applications in developing content.